The Influenz of Gen X And Gen Y on Motivation by Leadership Style - Rahayu, Jujuk Novi; Tridayanti, Hermien (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: Changes in the generation of human resources in an organization is something that cannot be avoided. Including the change of generations who hold the baton of leadership who have changed from generation X to the mayiritas gen Y, especially in managerial and top management positions. This study aims to analyze the influence of Gen X and Gen Y leadership on employee motivation through leadership style as an intervening variable, where the independent variable consists of Gen X leadership (X1), Gen Y leadership (X2), leadership style (Z) as an intervening variable and motivation (Y) as a dependent variable. Design/methodology/approach: This research is a quantitative research using the employee population in one of the salt industries in Indonesia at the level of supervisor, manager, and general manager. Findings: The results of this study show the direction of a positive variable relationship which means that the two variables are directly proportional, which means that Gen X leadership and Gen Y leadership affect employee motivation. Leadership style affects employee motivation. Gen X leadership influences employee motivation through leadership style and Gen Y leadership influences motivation through leadership style Research limitations/implications: This research was conducted on one of the companies in the salt industry in Indonesia by distributing questionnaires to 132 employees at the supervisor level as many as 77 people, managers 43 people and general managers as many as 12 people. The nature of the questionnaire shared is closed so that respondents only have to choose on the application of the selected answer. Practical implications: Changes that occur in the leadership variables of gen X will be followed by changes in employee motivation in the same direction if the leadership of Gen X is adequate in carrying out duties it will be followed by employee motivation, the existence of adequate Gen X leadership will be followed by high work motivation. The right leadership style can encourage Gen X to strengthen employee motivation. Changes that occur in the leadership variables of gen Y will have a good impact and will be followed by high employee motivation. A good leadership style will affect employee motivation. Changes in the leadership variables of gen Y will have an effect on changes in motivation variables in the direction, if the leadership of Gen Y runs well, it will have an impact on increasing employee motivation. The right leadership style can encourage Gen X to strengthen employee motivation. The right leadership style can support the implementation of the influence of gen Y leadership on employee motivation. Originality/value: This research was conducted in November – December 2023 at one of the salt industry companies in Indonesia by surveying at once 3 generations, namely gen X, gen y and gen z simultaneously to assess each of their leaders, both Gen X and Gen Y.